The Urgency of Morality and Social Norms in Campus Life - Wargo, Wargo; Abidin, Zaenal; Al-Munip, Al-Munip (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study seeks to explore the perceptions of students at the Al Mujaddid Islamic Institute Sabak regarding the urgency of morals and norms in campus life, addressing the gap between the recognized importance of ethical behavior and observed inconsistencies in moral practice among students. While higher education is often focused on cognitive development, less attention has been given to how moral values and social norms are internalized and practiced in daily campus interactions, particularly in Islamic-based institutions. This research employs a descriptive qualitative approach, with data collected through semi-structured interviews, classroom and campus observations, and document analysis. Data were analyzed using inductive thematic analysis, involving systematic coding, categorization of emerging patterns, and triangulation across sources to ensure credibility and a comprehensive understanding of students’ perspectives on moral and normative values. The findings indicate that most students perceive morals and norms as having a significant role in maintaining social harmony, academic ethics, and shaping their identity as Muslim students. However, challenges were also identified in the implementation of these values, such as the influence of popular culture, social media, and the lack of role models. The study highlights the importance of strengthening students’ awareness and internalization of moral values and norms in campus life, emphasizing the role of Islamic-based education, ethical practices, and social interactions in shaping a harmonious and responsible academic environment.